La brújula y el gusto: dos analogías para una aproximación realista a la experiencia moral - Asla, Mariano Gastón (Sapientia, 2022)
In this paper, I propose to use two analogies in order to offer a realistic characterization of moral experience. The analogy of the compass allows us to delve into the relationships between the notions of teleology (objective) and orientation (subjective), while that of taste brings to light the undeniable role of intuition and affectivity in the dictates of moral conscience. Finally, I will discuss my reflections with some moral theses of Francisco Leocata.